A comparative study of deep learning methods for automating road condition characterization - Ruhi, Zurana Mehrin; Sheetal, Farahatul Aziz; Prithu, Farisha Hossain (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.